La mostra ’Bologna Centro Storico’. Dalla politica del ‘buongoverno’ alla costruzione di un immaginario urbano - Cattabriga, Ilaria (Opus Incertum, 2024)
The paper deals with the case of the exhibition Bologna Centro Storico. Una città antica per una città moderna, held in Bologna in 1970. Promoted by the City Council, the exhibition aimed to illustrate to citizens the Plan for the Historic Center of Bologna (1969) designed by Pier Luigi Cervellati. Drawing on direct testimonies from the planners, the analysis of unpublished documents preserved at the Historical Archives of the Municipality and the Acer Archives, the paper delves into the assumptions and objectives of the plan, which formed the core content of the exhibition. It also investigates the exhibition’s design in terms of its sections, materials and multimedia tools. Among the devices used to revolutionize visitor engagement, the text especially focuses on the Implicor, an Olivetti machine designed to display part of the exhibition content. This device involved visitors in a new multimedia space that conveyed the future urban imaginary envisioned by the plan. The significance of Bologna Centro Storico within the broader context of urban plan exhibitions lies in its communicative techniques, which were employed to foster political consensus among the citizens, and to reassert the identity value of the historic center for the local community.